Manajemen Laba di Indonesia Signalling Ataukah Garbling? Peran Kontekstual Kualitas Audit dan Kinerja Perusahaan - Artika Enggar Dwiastuti (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2022)
The purpose of this study is to analyze the characteristics of the earnings management phenomenon in Indonesia, whether it refers to signalling or garbling and to find out the differences between the two characters through two other variables, namely audit quality and company performance. The sample of this research is 8 manufacturing companies that present financial reports on the IDX and issue bonds from 2012-2018. This study uses TZ statistics (Tucker & Zarowin) to measure earnings management. In this study, descriptive statistical tests with mean, maximum and minimum analysis tools were used to analyze the differences between companies with high yield and low yield. In relation to hypothesis testing, this study uses the non-parametric chi-square test. The results show that the phenomenon of earnings management characteristics of manufacturing companies listed on the IDX tends to be garbling in nature. This shows that investors in Indonesia are increasingly selective in making investment decisions. The results also show that there are differences in the level of audit quality and company performance in companies with signalling and garbling characteristics